Design and Implementation of Durable Road Infrastructure for Enhancing Rural Connectivity - Mohamad, Dadang (Global Writing Academica Researching & Publishing, 2023)
This study investigates the design and implementation of durable road infrastructure to enhance rural connectivity in Indonesia. Emphasizing the importance of robust infrastructure for socio-economic development, the research explores advanced materials and construction techniques aimed at increasing the longevity of rural roads. Using a mixed-methods approach, the study combines field surveys, laboratory testing, and case studies to evaluate the effectiveness of these methods. Key findings reveal that the application of geotechnical engineering principles and innovative pavement designs significantly improve road durability. The study also identifies critical factors influencing the success of road projects, including local environmental conditions and community involvement. Additionally, the research highlights the socio-economic benefits of improved road connectivity, such as increased access to markets, healthcare, and education. This paper provides practical recommendations for policymakers and engineers to optimize road infrastructure projects in rural areas, ultimately supporting sustainable rural development. The results underscore the need for tailored strategies that consider the unique challenges and opportunities of rural road construction.